P201 Parkrun dyspnoea – isn't it all exercise-induced asthma?. (15th November 2017) - Price, OJ; Darville, L; Allen, H; Hull, JH
Abstract : Introduction: A broad differential diagnosis exists for exercise-induced dyspnoea (EID) and wheeze in young athletic individuals, however these symptoms are often treated as presumed exercise-induced asthma (EIA). A key differential diagnosis for EIA is exercise-induced laryngeal obstruction (EILO); a condition characterised by transient closure of the larynx precipitating stridor during exercise. Recent studies reveal a prevalence of 5%–7% in Scandinavian adolescents, however the prevalence of EILO in the UK is currently unclear. Objectives: To assess the prevalence of stridor and EID in a cohort of recreationally active individuals. Methods: Cross-sectional field-based evaluation of the prevalence of stridor and EID in a cohort of individuals completing a 5 km Parkrun event in Northern England. Eighty-five adults (male: n=43) (mean ±SD) age: 39±15 years) were enrolled. Pre-race, respiratory symptoms (Dyspnoea-12 [D12 score:≥1–36] in combination with an Allergy Questionnaire for Athletes [AQUA score:≥5) and baseline spirometry were assessed. Immediately post-race, breathing was monitored continuously using an audio recording device for 15 min or until full recovery (i.e., resting tidal breathing had resumed). Recordings were analysed retrospectively and coded for signs of the predominant respiratory noise: 0=nil; 1=inspiratory stridor; 2=expiratory wheeze; 3=combined stridor+wheeze; 4=cough. Results: The majority of the cohort (93%) had normal resting lung function. Despite this, the prevalence of troublesome respiratory symptoms was 46% (D12 score: 6±5 and AQUA score: 13±6). Almost one third of the cohort (28%) had at least one respiratory sign: inspiratory stridor (n=9; 11%), expiratory wheeze (n=7; 8%), combined stridor +wheeze (n=6; 7%); cough (n=2; 2%). Of these, over one fifth (21%) had both a symptom and sign of respiratory dysfunction with sign of stridor and EID the most common (14%) (figure 1 ). Conclusion: The prevalence of stridor and EID was 14% in recreationally active individuals completing a Parkrun event. Further work is needed to determine if this relates to objective evidence of EILO however these findings indicate a prevalence in keeping with published series.